2015
DOI: 10.1161/strokeaha.115.008721
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Damage Relates to Oxygen Saturation in Children With Sickle Cell Anemia Without Silent Cerebral Infarcts

Abstract: Background and Purpose-Sickle cell anemia is associated with compromised oxygen-carrying capability of hemoglobin and a high incidence of overt and silent stroke. However, in children with no evidence of cerebral infarction, there are changes in brain morphometry relative to healthy controls, which may be related to chronic anemia and oxygen desaturation. Methods-A whole-brain tract-based spatial statistics analysis was carried out in 25 children with sickle cell anemia with no evidence of abnormality on T2-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 38 publications
(43 reference statements)
5
65
0
Order By: Relevance
“…Recently, decreased measures of O 2 saturation have been shown to correlate with compromised WM structure in SCD patients, supporting a role for acute-on-chronic hypoxia in white matter damage (Kawadler et al, 2015). …”
Section: Discussionmentioning
confidence: 96%
“…Recently, decreased measures of O 2 saturation have been shown to correlate with compromised WM structure in SCD patients, supporting a role for acute-on-chronic hypoxia in white matter damage (Kawadler et al, 2015). …”
Section: Discussionmentioning
confidence: 96%
“…White matter abnormalities from sickle vasculopathy have been reported in children with SCD despite lack of infarct observed on standard clinical MRI scans. Some uncertainty may be clarified with the shift to more powerful scanner magnets and/or use of additional MRI-based sequences and analytic methodologies [3436]. …”
Section: Discussionmentioning
confidence: 99%
“…Another TBSS study in 25 patients with no evidence of SCI showed FA significantly lower in cerebral peduncles and cerebellar white matter, whereas there were widespread increases in MD and RD across frontal and parietal lobes, corpus callosum and subcortical white matter. Furthermore, significant negative correlations were found between daytime peripheral oxygen saturation (SpO 2 ) and haemoglobin and RD in the anterior corpus callosum [96] (Figure 7). Results from a recent DTI-TBSS study [96], showing the white matter 'skeleton' (green) and significant correlations between RD and daytime peripheral oxygen saturation (blue) and haemoglobin (red).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 94%
“…Furthermore, significant negative correlations were found between daytime peripheral oxygen saturation (SpO 2 ) and haemoglobin and RD in the anterior corpus callosum [96] (Figure 7). Results from a recent DTI-TBSS study [96], showing the white matter 'skeleton' (green) and significant correlations between RD and daytime peripheral oxygen saturation (blue) and haemoglobin (red).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 94%